The complete mitochondrial genome of Epicauta ruficeps (Coleoptera: Meloidae) - Han, Xiaohong (Mitochondrial DNA B Resour, 2020)
Epicauta ruficeps is widely distributed in China and some countries in Southeast Asia, and plays an important role in medicine and biological control. The complete mitochondria genome of E. ruficeps was 15,813 bp in length, with 37 genes, including 13 PCGs, 22 tRNA genes (tRNAs), and two rRNA genes (rRNAs). The positions and sequences of genes were consistent with those of known Meloidae species. The nucleotide composition was highly A + T biased, accounting for ∼65% of the whole mitogenome. The complete mitogenome of E. ruficeps would help understand Meloidae evolution.